1976
DOI: 10.1159/000231708
|View full text |Cite
|
Sign up to set email alerts
|

E and EAC Rosette-Forming Cells in Healthy Donors and Cancer Patients

Abstract: The influence of age and sex on the lymphocyte count and numbers of E and EAC rosette-forming cells (RFC) was investigated using peripheral blood of healthy donors. In the female donors we found a lower total lymphocyte count and percentage of EAC RFC than in male donors. The percentage and total number of E RFC appeared to be low in younger donors. Total lymphocyte count and numbers of E and EAC RFC were investigated in untreated and treated patients with advanced solid tumors and in patients with untreated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…and serve as a surface marker for the earliest stage of the expression of hLiman T-Iincage cells (1)(2)(3). E-roscttes are widely used in clinical immunology lo identify or to separate T eells (4)(5)(6). although their precise intracellular mechanism is unknown.…”
Section: Participation Of Cytoplasmic Organelles In E-mentioning
confidence: 99%
“…and serve as a surface marker for the earliest stage of the expression of hLiman T-Iincage cells (1)(2)(3). E-roscttes are widely used in clinical immunology lo identify or to separate T eells (4)(5)(6). although their precise intracellular mechanism is unknown.…”
Section: Participation Of Cytoplasmic Organelles In E-mentioning
confidence: 99%
“…Some investigators have found depressed E-RFC levels in many patients with malignant tumors [3,6,9,14,16,28], while others have reported normal percentages of E-RFC in similar paReprint request shouM be addressed to: E. Ninger tients [8,15,17,23]. In most studies an increased frequency of depressed E-RFC values can be observed, but only in advanced stages of the disease.…”
Section: Introductionmentioning
confidence: 99%